Global DNA methylation and increased DNMT3A expression in multiple myeloma patients - Luzna, Petra; Weiser Drozdkova, Denisa; Flodrova, Pavla; Ondruskova, Katarina; Uberall, Ivo; Minarik, Jiri; Kolar, Zdenek; Smesny Trtkova, Katerina (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2023)
AIMS: The aim of this study was to compare the expression profile of selected DNA methyltransferases and global DNA methylation status in patients with different phases of multiple myeloma (MM) . For the analysis, different cellular populations including unsorted myeloma cells and a set of plasma cells purified by relevant antibodies were used. Consequently, laboratory data were compared to patients' clinical data. PATIENTS AND METHODS: For the analysis, unsorted bone marrow cell population of 44 MM patients (30 newly diagnosed, 9 relapsed and 5 patients in remission) and a set of 8 patients' samples of sorted plasma cells were used. We used commercially available RNA isolated from BM of 3 healthy individuals as control samples. Expression analysis of three DNA methyltransferases - DNMT1, DNMT3A, and DNMT3B was performed by quantitative RT-PCR and the patient global DNA methylation profiles were detected by colorimetric assay. RESULTS: Unchanged DNMT1 expression was detected in the selected cohort of patients. Normalized DNMT3A gene expression was globally higher in comparison with controls in unsorted and sorted cell populations. Low (0.08-1.81%) global DNA methylation status in unsorted samples of multiple myeloma patients did not correlate either with expression profiles of monitored DNA methyltransferases or with the stages of MM based on Durie-Salmon and International Staging System. CONCLUSION: This is the first comparative study between DNA methyltransferases expression profiles and global DNA methylation status in different phases of multiple myeloma patients. No significant correlation between the level of global methylation and the clinical stage of the unsorted cell population of patients with multiple myeloma was registered. Overexpression of the DNMT3A gene occurred in both sorted and unsorted cell populations of patients with multiple myeloma. This fact highlights the DNMT3A as a potential marker of multiple myeloma tumor progression. Moreover, we demonstrated comparable results in the expression of DNA methyltransferases in both sorted and unsorted cell populations. This is a promising result from the methodical point of view because when compared to samples of unsorted multiple myeloma cells, samples of sorted cells bring reduction of the number of possible analyses performed.
Keywords: DNA Methylation; mnohočetný myelom; multiple myeloma; DNA Methyltransferase 3A; Humans; Multiple Myeloma; metylace DNA; DNA methyltransferasa 3A; DNA methyltransferases; DNA; lidé; DNA methylation